2011
DOI: 10.1093/fampra/cmq111
|View full text |Cite
|
Sign up to set email alerts
|

The consultation as an interpretive dialogue about the child's health needs

Abstract: The study indicates that through open reflective dialogue the GP is able to assess the child and strengthen mutual trust in the doctor-parent relationship to the benefit of children with special needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…For example, in this study, the researcher identified text units in which the GPs describe their experiences using knowing-in-action mode and reflection-in-action mode. For more details see Lykke [17,19]. To ensure credibility and to control the researcher’s bias, the other authors reviewed parts of the transcripts and took part in the interpretation, development, and elaboration of the analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in this study, the researcher identified text units in which the GPs describe their experiences using knowing-in-action mode and reflection-in-action mode. For more details see Lykke [17,19]. To ensure credibility and to control the researcher’s bias, the other authors reviewed parts of the transcripts and took part in the interpretation, development, and elaboration of the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…This article draws on data from a qualitative study investigating GPs’ experiences of exploring a child’s wellbeing in the setting of a consultation [17-19]. The focus is on the child’s psychosocial health.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Lykke et al. found that subsequent consultations helped in involving parents in the assessment of the well-being of their children and that the continuity enabled the GP to bring up the difficult health issues over time [24]. Hence, it is important to further investigate how the balancing of trust and power is weighted with the severity of the health issue and the aspect of time.…”
Section: Discussionmentioning
confidence: 99%
“…One could argue that in this study, the use of humour was furthermore an indirect way of addressing a difficult or sensitive health issue. Other studies on GP’s perspectives suggest a concern among GPs on touching upon difficult or sensitive health issues in favour of maintaining a close relationship with their patients [12,14,16,23,24]. In these studies, the GPs expressed worries about intruding on the patient’s private life and harming the relationship when raising questions about sensitive or difficult health issues.…”
Section: Discussionmentioning
confidence: 99%
“…Asking participants to recount narratives based on experience also helps to elicit accounts that move beyond the socially acceptable or familiar 22. A study using focus groups to investigate child safeguarding by GPs in Denmark noted that the GPs appeared to be most comfortable with case-based discussion17 and this approach appeared to be acceptable to participants and to generate rich data in our two pilot interviews.…”
Section: Methodsmentioning
confidence: 99%